The development and op timisation of a Theiler's murine encephalomyelitis virus antiviral assay - Naidoo, Urisha Tirah (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Picornaviruses belong to the Picornaviridae family which are one of the largest and most diverse family of RNA viruses that cause a broad spectrum of infections in both humans and animals. These diseases range from severe infections such as poliomyelitis, meningitis, myocarditis to mild illnesses such as the common cold. Picornavirus outbreaks are a worldwide threat as they are continuously occurring. A recent outbreak of foot-and-mouth disease caused by a picornavirus occurred in South Africa, resulting in a temporary ban on the movement of cattle. Currently, the FDA has not approved any antiviral drugs against this virus, increasing the urgency for identifying effective antivirals. Picornaviruses have similar genomes and capsid organisation as such, those that are non-hazardous to humans can be used as a model system. A Theiler's murine encephalomyelitis virus (TMEV) strain GDVII and Baby Hamster Kidney fibroblasts (BHK-21 cells) was used as a replication system to develop and optimise a medium-throughput antiviral screening assay. The TMEV GDVII replication system in BHK-21 cells was validated, and preliminary experiments were performed that were necessary for the development of the TMEV GDVII antiviral assay. This was achieved by conducting a CPE assay to visually monitor the onset and development of CPE induced by TMEV GDVII. Plaque assays accurately quantified the number of infectious virus particles required for calculating the MOI in downstream experiments. Lastly, indirect immunofluorescence and Western blot analysis detected the expression of viral proteins using previously generated antibodies against the TMEV GDVII VP1 capsid and 2C protein, thereby confirming infection in BHK-21 cells. The development of robust and reproducible assays is an essential component in antiviral drug discovery. Therefore, the confirmed replication system was then used as a foundation to develop a medium-throughput CPE-based TMEV GDVII antiviral assay whereby the parameters were optimised to produce one of high quality. Firstly, the quantitation of viral-induced CPE was examined and confirmed in a 96-well plate using resazurin as a cell viability indicator. Each parameter was tested at varying conditions, and the optimal was concluded as 2 % FBS in the assay media, a 15 000 cells/well seeding density, infecting the cells with TMEV GDVII at an MOI of 0.00625 and measuring resazurin at an endpoint of 72 hpi. Furthermore, the parameters were ii validated by calculating the Z'- factor, which consistently produced scores above 0.5, indicative of a reliable, robust, reproducible antiviral assay. Currently, there are no inhibitors against TMEV GDVII that have been reported or confirmed in cell lines, animal models or clinical trials. Therefore, once the optimal assay parameters were selected, it presented an opportunity to assess whether potential compounds, including itraconazole (ITZ) and dipyridamole (DIP), possessed antiviral activity that could firstly, be utilised as a control inhibitor when screening compounds against TMEV GDVII and secondly, contribute to research on this virus. Additionally, the previously produced anti-TMEV GDVII capsid antibody was shown to neutralise viral infection and was also included as a potential control. The sensitivity of the cells towards DMSO, a solution in which the compounds were solubilised, was first investigated. It was found that concentrations above 1 % are toxic to the cells; as such, the final DMSO concentrations were always kept below 1 % when screening compounds. Lastly, the generation of dose-response curves aided in the conclusion that the antibody was the most suitable control inhibitor as it displayed potent antiviral activity and no cytotoxicity towards the cells. In contrast, ITZ and DIP did not possess effective antiviral action and were toxic to cells at high concentrations. Finally, after all the components of the medium-throughput TMEV GDVII antiviral assay were identified, it was possible to screen 24 compounds from a coumarin and marine natural product library for cell cytotoxicity and antiviral activity. After generating dose-response curves, it was concluded that no compound effectively inhibited virus-induced CPE, and most were toxic to cells at relatively high concentrations. In conclusion, this is the first study that describes the development and optimisation of a robust medium-throughput CPE-based antiviral assay that has immense potential to screen other libraries of compounds for antiviral activity against TMEV GDVII.
Keywords: Theiler's encephalomyelitis virus; Picornaviruses; Antiviral agents; Immunofluorescence; Western immunoblotting; Drug development